2019
DOI: 10.1089/lap.2018.0369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Operative Times and Mesh Utilization on Paraesophageal Hernia Repair: Analysis of 30-Day Outcomes from the American College of Surgeons National Surgical Quality Improvement Project Database

Abstract: Mesh utilization does not impact postoperative outcomes; however, as operative time increases, the incidence of postoperative morbidity also increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In both surveys of the SAGES community, mesh types were heterogeneous although biologic meshes were most commonly used [4,5] . Similar results were found in a survey of the European Association for Endoscopic Surgery (EAES) in 2015, with higher use of mesh at 92.1% of European surgeons at least selectively using mesh although mesh types differed with most surgeons preferring either polypropylene, polyester or PTFE meshes and only 27.9% using biologic meshes [6] . In registry analyses, these survey results are further expanded: mesh is used frequently but in less than half of ARS cases overall [7][8][9][10] .…”
Section: Trends Of Mesh Use In Arssupporting
confidence: 77%
“…In both surveys of the SAGES community, mesh types were heterogeneous although biologic meshes were most commonly used [4,5] . Similar results were found in a survey of the European Association for Endoscopic Surgery (EAES) in 2015, with higher use of mesh at 92.1% of European surgeons at least selectively using mesh although mesh types differed with most surgeons preferring either polypropylene, polyester or PTFE meshes and only 27.9% using biologic meshes [6] . In registry analyses, these survey results are further expanded: mesh is used frequently but in less than half of ARS cases overall [7][8][9][10] .…”
Section: Trends Of Mesh Use In Arssupporting
confidence: 77%
“…As a risk factor of postoperative morbidities and readmission ( 31 , 32 ), operative time also represents an important parameter examined in our study. Simplifying the step of closing the free peritoneal flap was expected to reduce the operative time and therefore, leaving the free peritoneal flap in place provides this advantage ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Applying the results of Skancke et al, 4 of the 5 cases would fall into the fourth quartile of all operative times for PEHR, whereas the remaining case would fall in the third quartile. 21 PEHR currently does not have a gold standard for describing case complexity. As it relates to predicting PEs, a number of other factors of case complexity could be considered such as reoperative surgery, acute presentation, hernia size, and need for the mesh.…”
Section: Discussionmentioning
confidence: 99%
“…11 Though, the 1 "moderate" risk patient also happened to be the patient with the longest case duration and arguably most technically challenging anatomy. In fact, the average PEHR patient in this country would be classified as "high" risk by the Caprini model for age, BMI, and operative length alone (age, 61 to 74 y: 2 points; laparoscopic surgery > 45 min: 2 points; BMI > 25, 1 point) as Skancke et al 21 reported mean age of 64 years, mean BMI of 31, and median operative length of 142 minutes. The ACCP guidelines recommend pharmacologic prophylaxis in "high" risk patients with the overwhelming majority of trials demonstrating benefit applying administration 2 hours preoperatively.…”
Section: Discussionmentioning
confidence: 99%